Genomic characterisation of invasive non-typhoidal Salmonella enterica Subspecies enterica Serovar Bovismorbificans isolates from Malawi. - Christina Bronowski; Maria C Fookes; Ruth Gilderthorp; Kevin E Ashelford; Simon R Harris; Amos Phiri; Neil Hall; Melita A Gordon; John Wain; Charles A Hart; Paul Wigley; Nicholas R Thomson; et al. (PLoS Neglected Tropical Diseases, 2013)
Invasive Non-typhoidal Salmonella (iNTS) are an important cause of bacteraemia in children and HIV-infected adults in sub-Saharan Africa. Previous research has shown that iNTS strains exhibit a pattern of gene loss that resembles that of host adapted serovars such as Salmonella Typhi and Paratyphi A. Salmonella enterica serovar Bovismorbificans was a common serovar in Malawi between 1997 and 2004.We sequenced the genomes of 14 Malawian bacteraemia and four veterinary isolates from the UK, to identify genomic variations and signs of host adaptation in the Malawian strains.Whole genome phylogeny of invasive and veterinary S. Bovismorbificans isolates showed that the isolates are highly related, belonging to the most common international S. Bovismorbificans Sequence Type, ST142, in contrast to the findings for S. Typhimurium, where a distinct Sequence Type, ST313, is associated with invasive disease in sub-Saharan Africa. Although genome degradation through pseudogene formation was observed in ST142 isolates, there were no clear overlaps with the patterns of gene loss seen in iNTS ST313 isolates previously described from Malawi, and no clear distinction between S. Bovismorbificans isolates from Malawi and the UK. The only defining differences between S. Bovismorbificans bacteraemia and veterinary isolates were prophage-related regions and the carriage of a S. Bovismorbificans virulence plasmid (pVIRBov).iNTS S. Bovismorbificans isolates, unlike iNTS S. Typhiumrium isolates, are only distinguished from those circulating elsewhere by differences in the mobile genome. It is likely that these strains have entered a susceptible population and are able to take advantage of this niche. There are tentative signs of convergent evolution to a more human adapted iNTS variant. Considering its importance in causing disease in this region, S. Bovismorbificans may be at the beginning of this process, providing a reference against which to compare changes that may become fixed in future lineages in sub-Saharan Africa.